2022
DOI: 10.1021/acs.biomac.2c00878
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Microneedle Arrays with Glucose-Sensing Dynamic-Covalent Bonding for Insulin Delivery

Abstract: The ongoing rise in diabetes incidence necessitates improved therapeutic strategies to enable precise blood glucose control with convenient device form factors. Microneedle patches are one such device platform capable of achieving therapeutic delivery through the skin. In recent years, polymeric microneedle arrays have been reported using methods of in situ polymerization and covalent crosslinking in microneedle molds. In spite of promising results, in situ polymerization carries a risk of exposure to toxic un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…Recent decades have seen a dramatic rise in the incidence of diabetes, and with it an increased focus on new routes for insulin delivery to improve treatment. Glucose-responsive technologies and delivery approaches, including those based on hydrogels, constitute one ongoing effort to better recreate and replace the natural temporal signaling of insulin with more biomimetic therapeutics. In this regard, dynamic-covalent bonding between phenyboronic acids (PBAs) and cis- 1,2 or cis- 1,3-diols offers one of the most commonly explored approaches to achieve glucose-responsive function. , PBAs are Lewis acids that form dynamic-covalent complexes with diols at pH values near or above a specific p K a governing the equilibrium between their neutral trigonal form and their anionic, diol-binding tetrahedral form; the PBA–Diol bond is furthermore susceptible to competition from ambient glucose, itself a cis- 1,2 diol . PBA–Diol bonds have thus been used to prepare hydrogels formed by dynamic-covalent cross-linking in order to afford glucose-responsive features such as network swelling, gel erosion, and the release of encapsulated insulin or other payloads. …”
Section: Introductionmentioning
confidence: 99%
“…Recent decades have seen a dramatic rise in the incidence of diabetes, and with it an increased focus on new routes for insulin delivery to improve treatment. Glucose-responsive technologies and delivery approaches, including those based on hydrogels, constitute one ongoing effort to better recreate and replace the natural temporal signaling of insulin with more biomimetic therapeutics. In this regard, dynamic-covalent bonding between phenyboronic acids (PBAs) and cis- 1,2 or cis- 1,3-diols offers one of the most commonly explored approaches to achieve glucose-responsive function. , PBAs are Lewis acids that form dynamic-covalent complexes with diols at pH values near or above a specific p K a governing the equilibrium between their neutral trigonal form and their anionic, diol-binding tetrahedral form; the PBA–Diol bond is furthermore susceptible to competition from ambient glucose, itself a cis- 1,2 diol . PBA–Diol bonds have thus been used to prepare hydrogels formed by dynamic-covalent cross-linking in order to afford glucose-responsive features such as network swelling, gel erosion, and the release of encapsulated insulin or other payloads. …”
Section: Introductionmentioning
confidence: 99%
“…We synthesized five different fluorescent PBA probes from 4-carboxyphenylboronic acid and its derivatives bearing various substituents at the meta position (Figures 2b and S2.1−S2. 19). Ortho-substitutions to the boronic acid were avoided to minimize additional variables, such as steric strain, which could limit the desired π-conjugation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In our previous study, boronic acids have been shown to react with teichoic acid diols in bacterial cell walls and were harnessed as a reliable chemical handle for material synthesis . Prior works in boronic acid-bearing polymers yielded self-healing hydrogels, glucose-responsive materials, and recyclable polymers through their reactivity toward diol and polyol species. Application of this dynamic covalent chemistry at the interface between macromolecules and engineered bacterial spores should therefore offer a powerful method to access functional spore-based materials with all the tunability and sustainability merits of abiotic dynamic covalent networks, such as self-healing, adaptiveness, and on-demand recycling.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic-covalent bond between a phenylboronic acid (PBA) and a cis-1,2 or cis-1,3 diol has been widely explored in preparing glucose-responsive materials due to its susceptibility to competition from free glucose. [26][27][28][29][30][31][32] The PBA-diol interaction is also sensitive to environmental parameters such as pH or temperature, with bonds formed more readily in pH conditions at or above the pK a of the specic PBA motif and bond dynamics being accelerated with increased temperature. This has led to the preparation of biomimetic PBA-diol crosslinked hydrogels responsive to a variety of stimuli.…”
Section: Introductionmentioning
confidence: 99%